Can small scale farmers benefit from biotechnology? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Malawi, faced with a crisis situation, accepted genetically modified food aid, despite misgivings from some scientists. Dr Sosten Chiota is an environmental scientist at the University of Malawi.